Anatomia radiológica da placa de crescimento dos ossos longos em potros crioulos - Luiz, Rodrigo Colares (2005)
With the objective of documenting the moment of closing of the physeal plates of the bones, this study used 92 foals of the creollo breed aged between 6 and 29 months. Using the ante-posterior projection, radiographic images were taken of the anterior and posterior members of both sexes for the distal portion of the radial, the 3rd metacarpal and the distal aspect of the tibia. The ante-posterior radiographic projection was utilized in all cases. The radiographic image of the growth plate was classified as visible, partially visible or not visible. At 7 months the growth plate of the principal metacarpal was not visible. In the distal physis of the tibia it was not possible to identify it at 23 months. In the distal aspect of the radius it was visible at age 25 months.